2009
DOI: 10.1128/aem.02634-08
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Improvement and Evolution of Atrazine Chlorohydrolase

Abstract: The atrazine chlorohydrolase AtzA has evolved within the past 50 years to catalyze the hydrolytic dechlorination of the herbicide atrazine. It is of wide research interest for two reasons: first, catalytic improvement of the enzyme would facilitate its application in bioremediation, and second, because of its recent evolution, it presents a rare opportunity to examine the early stages in the acquisition of new catalytic activities. Using a structural model of the AtzA-atrazine complex, a region of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 59 publications
6
38
1
Order By: Relevance
“…To improve the yield of its soluble form, we performed laboratory evolution, using a method that we have previously used with related metallohydrolases from Pseudomonas sp. strain ADP (AtzA [atrazine chlorohydrolase]) and Agrobacterium radiobacter (phosphotriesterase) (5,57). This involved screening libraries of random variants using an agar plate-based activity screen in which substrates were included in the agar gel at concentrations in excess of the solubility limit, resulting in opaque plates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the yield of its soluble form, we performed laboratory evolution, using a method that we have previously used with related metallohydrolases from Pseudomonas sp. strain ADP (AtzA [atrazine chlorohydrolase]) and Agrobacterium radiobacter (phosphotriesterase) (5,57). This involved screening libraries of random variants using an agar plate-based activity screen in which substrates were included in the agar gel at concentrations in excess of the solubility limit, resulting in opaque plates.…”
Section: Resultsmentioning
confidence: 99%
“…These metal ions can play structural or catalytic roles, and their incorporation into apoenzyme folding intermediates is an important step in the overall folding pathway (2). One of the most diverse superfamilies of enzymes, which includes a large number of microbial enzymes that are capable of catalyzing the hydrolysis of toxic synthetic compounds (3)(4)(5), is the metal ion-dependent amidohydrolase superfamily (6,7). Unfortunately, many of these proteins form insoluble aggregates or are produced only at very low levels when overexpressed in recombinant systems.…”
mentioning
confidence: 99%
“…Placement of the ametryn and atratone in the active site also agreed with initial docking studies with only slight differences in the conformation of the alkyl groups (data not shown). Note that a published homology modeled structure of AtzA showed the alkyl groups in the opposite orientation with respect to the conserved active-site glutamate (40). This conformation is not likely as one of the N-alkyl binding pockets is clearly smaller than the other.…”
Section: Table 3 Kinetic Constants For Wild-type and Mutant Trzn Withmentioning
confidence: 99%
“…Combining rational engineering principles with an evolutionary approach has proven particularly powerful: small focused libraries are synthesised, guided by structure-function information, and then screened/ selected for properties of interest 10 . Such strategies have been used to alter properties such as stereospecificity, expression level 11 and Michaelis constants (K M ) 12 and to overcome functional constraints, such as inhibition by substrates and/or products leading to improved reaction yields 13 .…”
mentioning
confidence: 99%